LEGAL PROTECTION OF CONSTITUTIONAL RIGHTS OF INDIGENOUS CHILDREN’S INDIGENOUS LEGAL COMMUNITIES IN MUSI RAWAS UTARA REGENCY, SOUTH SUMATERA PROVINCE - Wawan Fransisco (PRANATA HUKUM, 2022)
A group of people who have the same feelings in a group, living in one place due to genealogy or geological factors is a Customary Law Community. the rules regarding rights and obligations on material and immaterial goods are already owned in their own customary law. the normative legal writing method because it examines statutory regulations, literature, and journals and papers related to the material under study, which consists of the types of data obtained in this study are secondary data, namely data obtained from library research and documentation, which is the results of research and processing of others, which are already available in literature or documentation. Protection for indigenous peoples as regulated in Article 28I paragraph (3) as well as in Article 18 B (2) of the 1945 Constitution and operational regulations are very necessary so that Indonesian legal order can be implemented properly. This problem is because the amendments to the 1945 Constitution at that time were laden with the interests of the administrators at that time. On the other hand, the state also recognizes and respects the rights of indigenous peoples, as well as on the other hand, they are required to fulfill the requirements to realize their rights.